A thaw in relations between Egypt and Turkey: Weaknesses in foreign policy and the economy bring the regimes in Cairo and Ankara closer together - Hürcan Aslı Aksoy; Stephan Roll (Stiftung Wissenschaft und Politik (SWP), 2021)
The visit of a high-ranking Turkish delegation to Cairo in early May 2021 indicates a turning-point in the relations between Turkey and Egypt. Since the 2013 military coup in Egypt, the leaders of these two Mediterranean countries had been extremely hos-tile towards each other. The current rapprochement, which might lead in a best case scenario to a resumption of diplomatic relations, thus comes as a surprise. But it is limited in scope. The main obstacles to a closer partnership between Recep Tayyip Erdoğan and Abdel Fatah al-Sisi are differences in the ideological foundations of their regimes. The aim of these current shifts in foreign policy is to increase the presidents' room for manoeuvre. Their regimes are under pressure due to regional, international, and domestic developments. Germany and the EU should support the normalisation attempts because they can contribute to de-escalation in the region. Both regimes' current weaknesses in foreign policy and the economy provide an opportunity to call for political change in other areas.
Keywords: 320